COVID-19 and Bangladesh: Challenges and How to Address Them - Anwar, Saeed; Nasrullah, Mohammad; Hosen, Mohammad Jakir (Frontiers in Public Health, 2020)
• As the coronavirus outbreak quickly surges worldwide, many countries are adopting non-therapeutic preventive measures, which include travel bans, remote office activities, country lockdown, and, most importantly, social distancing • However, these measures face challenges in Bangladesh, a lower-middle-income economy with one of the world’s densest populations • Social distancing is difficult in many areas of the country, and with the minimal resources the country has, it would be extremely challenging to implement the mitigation measures • Mobile sanitization facilities and temporary quarantine sites and healthcare facilities could help mitigate the pandemic impact at a local level • A prompt, supportive, and empathic collaboration between the government, citizens, health experts, along with international assistance, can enable the country to minimize the impact of the pandemic